Knitting Skill Training for PKK Members in Sungai Pauh Pusaka Village Langsa City - Rizky Nafaida; Hartutik Hartutik; Nursamsu Nursamsu (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This community service aimed to address challenges PKK members face in Sungai Pauh Pusaka Village, including a need for knitting skill training and knowledge. The goal was to empower these members with practical skills to create knitting products, enhancing their self-sufficiency and village development. Method: The project involved stages like preparation, implementation, and evaluation. Coordination with the PKK head set the schedule. Training included tools and material introduction. Satisfaction surveys gauged participant motivation. Practical Applications: The practical applications of this community service initiative are noteworthy. It has empowered PKK members with valuable knitting skills, making them more self-sufficient and capable of creating knitting products. These newfound skills can be applied in various real-world scenarios, potentially leading to economic opportunities for the participants and contributing to the development of Sungai Pauh Pusaka Village. Conclusion: The initiative achieved an 80.0% satisfaction rate, highlighting the success of University Samudra's knitting skill training in empowering PKK members and benefiting the community.